An enhancement of the random sequence 3-level obfuscated algorithm for protecting agents malicious hosts - Abu Bakar, Kamalrulnizam; Bernard, S. Doherty (Agora University Editing House, 2007)

(untitled)
With the advent of agent technology, the need for security of applications becomes a concern that is beyond classical data security capability and considerations. Without proper security protection especially against a malicious host attack, the widespread use of agent technology can be severely impeded. The Random Sequence 3-level obfuscated algorithm has been proposed by the authors to improve agent security: in this paper, an enhancement to the protection level of this algorithm is proposed. The effectiveness of the obfuscation algorithm is enhanced by addition of noise, which surrounds the true value carried by the agent with false values. A malicious host can thus at best guess the true value carried by the agent.